2008
DOI: 10.1080/10875540801973542
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of State Minimum Wages on Child Poverty in Female-Headed Families

Abstract: Several state governments set minimum wage levels above the federal level, and some automatically index them to inflation. This article uses the variation in real minimum wages both over time and across states to examine how minimum wages have affected poverty rates of children living in female-headed households. These children are among the most vulnerable members of society and are increasingly likely to feel the impact of such policy actions due to the growing presence of their mothers in low-wage labor mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
1
6
0
2
Order By: Relevance
“…A sizable proportion of those studies cannot identify significant effects on the reduction of poverty (Vedder and Gallaway, 2002;Neumark and Wascher, 2002;Burkhauser and Sabia, 2007;Sabia, 2008;Sabia and Burkhauser, 2010;Sabia and Nielsen, 2013). Other studies find moderate, yet statistically significant reductions for the incidence (Addison and Blackburn, 1999;Morgan and Kickham, 2001;Stevans and Sessions, 2001;Gundersen and Ziliak, 2004;DeFina, 2008;Sen et al, 2011) and depth of poverty (Dube, 2018) in the U.S. Neumark et al (2012) identify a slight poverty-reducing effect of city-wide living wage laws.…”
Section: Literaturementioning
confidence: 99%
“…A sizable proportion of those studies cannot identify significant effects on the reduction of poverty (Vedder and Gallaway, 2002;Neumark and Wascher, 2002;Burkhauser and Sabia, 2007;Sabia, 2008;Sabia and Burkhauser, 2010;Sabia and Nielsen, 2013). Other studies find moderate, yet statistically significant reductions for the incidence (Addison and Blackburn, 1999;Morgan and Kickham, 2001;Stevans and Sessions, 2001;Gundersen and Ziliak, 2004;DeFina, 2008;Sen et al, 2011) and depth of poverty (Dube, 2018) in the U.S. Neumark et al (2012) identify a slight poverty-reducing effect of city-wide living wage laws.…”
Section: Literaturementioning
confidence: 99%
“…As I discuss in online Appendix A, a number of researchers have studied the impact of minimum wages on children and single mothers (e.g., Morgan and Kickham 2001, DeFina 2008, Gundersen and Ziliak 2004. Several studies have also considered younger adults, or adults with limited education; these include Neumark (2016), Addison and Blackburn (1999), and Sabia and Nielsen (2015).…”
Section: Data and Research Designmentioning
confidence: 99%
“…Similarly, Misra et al found that in countries with more generous family benefits and child‐care subsidies, young children—particularly those living with single mothers—were at less risk of poverty. Comparative research on disparities between U.S. states has also revealed the importance of state policies in predicting child poverty rates over time (DeFina, 2008; Morgan & Kickham, 2001).…”
Section: Causes Of Povertymentioning
confidence: 99%